Exploring the factors influencing UPM English language faculty members' adoption and integration of web-based instruction (WBI) - Sayadian, Sima; Mukundan, Jayakaran; Baki, Roselan (The Clute Institute, 2009)
Technology, if integrated effectively, has been found to influence students' academic performance, develop their higher order thinking and problem solving, improve their motivation, attitude, and interest in learning, and help them prepare for the workforce as well as address the needs of low performing, at-risk, and learning impaired students (Center for Applied Research in Educational Technology, 2005). This paper reports the findings of the study trying to investigate the application and integration of web based instruction by University Putra Malaysia (UPM) lecturers in Serdang, Malaysia. A questionnaire which included the items from the short form of the Moore and Benbasat (1991) instrument as well as some demographic questions was administered to UPM lecturers in Malaysia. Data collected through the survey questionnaire was used to examine the factors influencing the University Putra Malaysia (UPM) lecturers' perception about application and integration of web based instruction. Our analysis of the data suggests that the innovation adoption variables of relative advantage, compatibility, visibility, ease of use, results demonstrability, and trialability should be considered by university lecturers seeking to increase the rate of adoption of e-Learning within their organisation.